Implementasi Discovery Learning untuk Meningkatkan Kecerdasan Digital Mahasiswa - Lathifah, Afra; Kurnia, Ulfa Isni; Hertati, Elvani (Infotek: Jurnal Informatika dan Teknologi, 2025)
The digital era demands students to have comprehensive digital intelligence, including students' ability to access, manage, analyze, and present digital information, alongside a grasp of digital ethics and safety. This research seeks to examine how the Discovery Learning approach influences the enhancement of students' digital intelligence. The study employed a pre-experimental design utilizing a one group pretest-posttest, which included 31 students in their fifth semester from the Faculty of Teacher Training and Education. The results showed a significant increase in students' digital intelligence. Statistical analysis produced a significance probability of p = 0.0000 (p <0.05), an average increase of 25.01%. Through the stages in this model, students are given the opportunity to not be passive in the learning process, so they can have critical thinking skills, problem solving, and digital skills needed in today's digital era. Further research should explore other elements, including lecturer readiness, availability of digital learning resources, and supportive institutional policies